Ryzyko autorytaryzmu w idei i praktyce uczenia się przez całe życie - Jędrzejczak, Helena Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2023)
The article addresses the issue of Lifelong Learning (LLL) as an idea and practice. This issue has been the subject of public policies since the 1960s. In the related discourse, it is seen not so much as a practice of choice or necessity, but as an autotelic value with an unambiguously positive character. Representatives from the social sciences and humanities dispute with this view, pointing to its subordination to a neoliberal vision of the world, the shifting of responsibility entirely to the individual and the creation of discourse and practices in such a way that educational behaviour serves the needs of the state rather than those of the people. The article also takes a critical look at the idea of LLL, but from a different perspective. John Rawls’ theory of justice, Isaiah Berlin’s concept of freedom and Karl Mannheim’s notion of utopia are used to analyse the nature and consequences of the idea of LLL. Within such an ideological context, a reflection was undertaken on how the dominant understanding of LLL captures the relationship between people and between the state and the individual, and how its utopianism may foster subordination to authoritarianism by male and female citizens. The final section of the article identifies how texts by philosophers Berlin, Rawls and Mannheim offer a way of countering this.
Keywords: lifelong learning; democracy; John Rawls; Isaiah Berlin; utopia; critical analyses of ideas